International legal personality of Prophet Muḥammad (pbuh) - Mohd Kamal, Mohd Hisham (IIUM Press, International islamic University Malaysia, 2017)
An international legal person is a subject of international law who enjoys rights, duties or powers in international law and the capacity to act on the international plane. Under modern international law, States are international persons, whereas private individuals are not. This article discusses whether Prophet Muḥammad (pbuh) of the religion of Islam was an international legal person. Evidence shows that his correspondences with other States and nations were in his name “Muḥammad ibn ‘Abdullāh” or “Muḥammad the Messenger of Allah,” and not as the head of the City-State of Medina. Was he recognised as such by the international community at that time? This work finds that Prophet Muḥammad (pbuh) was accepted by the international community during his time as an international legal person. His personality was due to his unique position as a prophet.